Organic Beekeeping and Honey Production Approach in Iğdır Region of Türkiye - Fatih Araz; Başaran Karademir; İbrahim Hakkı Kadirhanoğulları (Turkish Journal of Agriculture: Food Science and Technology)
Organic agricultural products are food products that are inspected and certified at all stages of production until they are offered for consumption by institutions that are authorized by the state. Beekeeping products made for human food are also subject to the same certification process. With this research, it was aimed to reveal the organic beekeeping and organic honey understanding of the people of Iğdır region. With the survey, the information of the local consumers about organic honey, how they got this information, their status and reasons for organic honey consumption, as well as the certification processes were collected. The obtained data were analyzed with numerical, proportional, and decision tree methods. The genders of the survey participants were 66% male, 34% female. It was also determined that 70.5% of the participants were under the age of 40, had a bachelor's degree or higher education level in the proportion of 43%, and 63% had a minimum wage or lower-income level. For the questions asked about the research topic, it was reported that participants know and eat organic honey in the proportion of 93%, buy organic honey in the proportion of 77.5%, having information about the organic honey certificate in the proportion of 67% and certification stages in the proportion of 43%. Despite these high rates, the same participants gave contradictory answers to some other questions, such as; for the question of “What is organic honey?” the answer of "Certified honey" in the proportion of only 11.5% and for the question of “How did you know that the organic honey you bought was organic honey?” the answer of " I saw its certificate” in the proportion of only 18.1%. This contradiction was noted. With this research, it was determined that the local people did not have enough information about organic beekeeping and honey understanding. In order to fill this gap, it can be suggested that healthy nutrition lessons be included in the education curricula starting from primary school, and usage of TV, radio, and internet broadcasting for this purpose. The fact that the participants' education level is high and their age is young may provide an advantage in order to get results from the training to be given on the subject.